THE EFFECT OF VARIED CONCENTRATION AND SOAKING TIME IN THE SOLUTION OF LIQUID SMOKE PYROLIZED FROM PEANUT SHELL (Arachis hypogea) ON THE QUALITY OF SMOKED CATFISH (Mystus nemurus) - Roni Andika; Sukirno Mus; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research had been conducted in November 2014 in purpose todetermine the effect of varied concentration and soaking time in liquid smokesolution pyrolyzed from peanut shell (Arachis hypogea) on the quality of smokedcatfish (Mystus nemurus). The method used in this study was experimental anddesigned as Completely Randomized Design (CRD) composed factorially 2x2. Thecatfish was soaked in a solution of liquid smoke with different concentrations 8%(K8) and 12% (K12) for 60 minutes (L60) and 90 minutes (L90), an then dried usingan oven at a temperature of 55ºC for 12 hours. The quality parameters weretheorganoleptic, chemical, total phenols, total acids, and pH values. The resultsshowed that the differences of concentrations and soaking time in a solution ofliquid smoke affected significantly on the quality of smoked catfish as shown onthe score of the texture and odor, moisture, but not significantl affected on thescore of appearance and taste, total phenols, total acids and pH values. Thetreatment K12L90 showed the best quality of smoked catfish with the score of odor7.64 and taste 7.32, moisture content 8.24%, total phenols 0.11ppm, and totalacids 9.16%, meanwhile the second best quality of the smoked catfish was shownby the treatment K8L60 with the score of appearance 7.23, and pH value 6.21.Thesensory characteristics of smoked catfish was showing that the meat surface wasclean, neat , and had attractive colors (golden yellow), had the specific odor ofsmoked fish, had delicious taste and distinctive flavor of smoked fish, less salty,and had a compact and soft texture of the meat.Keywords: liquid smoke, Mystus nemurus, peanut shell, soaking time, solutionconcentration